(g-f)(x)=g(x)=f(x)
(g-f)(x)=6x-4+x^2
(g-f)(x)=x^2+6x-4 then:
(g-f)(3)=3^2+6*3-4
(g-f)(3)=9+18-4
(g-f)(x)=23
The answer is
C) -7
Multiply -5 by 2
Divide 8 by 4 :
3-10+2-2
Subtract 10 from 3 :
-7+2-2
Add -7 and 2 :
-5 - 2
Subtract 2 from -5:
-7
The answer to your question is 7a.
Answer:
1 9/16
Step-by-step explanation:
F(1/4) means u plug in 1/4 for x
so the equation would be
f(1/4)=1/4^2+2 1/4 + 1
f(1/4)=1/16+1/2+1
f(1/4)= 9/16 +1
f(1/4)= 1 9/16
its not nine teen its one and 9 over 16 just clarification
answer is f hope u like it plz mark me as brainliest plzzzzzzzzzzzzz